Pengaruh pola asuh orang tua pada pembentukan kepribadian anak - Khasanah, Faidatul (Maliki Interdisciplinary Journal, 2024)
This study aims to analyze the influence of parenting styles on children’s personality development. Parenting styles, including authoritative, authoritarian, permissive, and neglectful, play a significant role in shaping a child’s character and socio-emotional development. Data were obtained through a literature review of previous studies that examined the relationship between parenting styles and children’s psychosocial development. The analysis reveals that authoritative parenting has the most positive impact, fostering independent, confident, and socially adaptive children. Conversely, authoritarian and permissive styles tend to have negative effects, such as low self-esteem and behavioral issues. This study emphasizes the importance of applying balanced parenting to support optimal child development.